Determination of the content of free and attached moisture in spent grain - A. S. Danilchenko; Kh. R. Siyukhov; T. G. Korotkova; B. B. Siyukhova (Новые технологии)
Experimental data on the kinetics of drying of raw brewer’s grains from the Maykop brewery for two temperature regimes of 60°C and 55°C are presented. The dry matter content is 12,7%. The drying agent speed is 4,5 m/s. The purpose is to determine the content of free and attached moisture in brewer’s grains obtained as a waste in the production of beer using classical technology. Analysis of the drying curves and drying rate curves has shown that free moisture is removed when the moisture content changes from the initial 687,4% to 360%; with a further decrease in the moisture content, the attached moisture is removed. A moisture content of 360% is assumed to be at the interface between the first and second drying periods. The average free moisture content is 47%, that of the attached one is 53%. A significant amount of the attached moisture indicates insufficient destruction of the cellular structure of the material.